2016
DOI: 10.4236/as.2016.74026
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Plant Spacing under the Systems of Rice Intensification (SRI)

Abstract: Optimum plant spacing is among key agronomic parameters that influence crop growth performance and crop yield. A study was conducted to investigate the optimum rice transplanting spacing under the Systems of Rice Intensification (SRI) practice in Tanzania. The study composed of five treatments of rice transplanting spacing namely 1) 15 cm × 15 cm (T1); 2) 20 cm × 20 cm (T2); 3) 25 cm × 25 cm (T3); 4) 30 cm × 30 cm (T4); and 5) 35 cm × 35 cm (T5). The experiment was set in a Randomized Complete Block Design (RC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…In terms of yield components, different spacings resulted in different grains filling capabilities between varieties. [29,30] reported the same thing. The total assimilation tends to affect the ability to fill the bigger grains.…”
Section: Yield Componentsmentioning
confidence: 71%
“…In terms of yield components, different spacings resulted in different grains filling capabilities between varieties. [29,30] reported the same thing. The total assimilation tends to affect the ability to fill the bigger grains.…”
Section: Yield Componentsmentioning
confidence: 71%
“…The increase of yields was due to good neutralization of resources, recommended spacing for crops increased yields [28]. Other study [29] reported using of recommended spacing facilitates the growth of crops and produce high yield since crops grows with good management practice.…”
Section: Discussionmentioning
confidence: 99%
“…In this preliminary finding, we speculated that the existence of high unproductive tillers under double row spacing became key factor in hill strength. Nevertheless, it is generally concluded that large number of unproductive tiller competes with final rice production (Wang et al, 2007;Badshah et al, 2014;Reuben et al, 2016). Therefore, it needs further evaluation by using larger number of rice genotypes to reveal the role of unproductive tiller andhill aerodynamic, and to figure out reasonable number of unproductive tiller.…”
Section: Hills Damage and Its Implicationmentioning
confidence: 99%